Ways to Return to Allah in the Exhibition of the Qur’an - An Objective Study - Hammad , Laith (Islamic Sciences Journal, 2023)
ABSTRACT The subject of research which concerns the sciences of the Qur’an and its interpretation is entitled "Methods of returning to Allah in the Qur’anic exhibition - an objective study". The research includes the verses ending with (Perhaps they return) which in their content and meanings' connotations is a call for humanity to give up disobedience, sins and all kinds of corruption, and to return to Almighty Allah. These verses follow the style of Herald and reward at times and in the manner of warning and torment at other times. Some people knew, concerned and believed, while some other condemned and insisted and disbelieved, so Allah tormented them, and ended their lives with the end of evil. He tormented them in their lives with hard torment which though hard but still non- comparable in severity and cruelty with that of the Hereafter. I present this study as a reminder and consideration for me and for others, hoping the mercy and pardon of Allah. Thus, I put a research plan commensurate with the meanings of the verses and their connotations that are related to the research. The plan included a preview, two chapters, and then reaching a set of results, which show the importance of the research, and their benefits.